2020
DOI: 10.1186/s12871-020-01129-0
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil postoperative analgesia reduce the increase of T helper 17 (Th17) cells and FoxP3+ regulatory T (Treg) cells in rat hepatocellular carcinoma surgical model: A randomised animal study

Abstract: Background: Surgery-related pain and opioids might exacerbate immune defenses in immunocompromised cancer patients which might affect postoperativd overall survival. Sufentanil is a good postoperative pain control drug,the present study aimed to figure out whether it effect T cell immunity in rat hepatocellular carcinoma surgical model. Methods: A rat hepatocellular carcinoma (HCC) models was established by N-nitrosodiethylamine. Forty-eight of them were randomly divided into 3 equal groups: surgery without po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“… 27 Moreover, sufentanil may decrease the CD4 + /CD8 + ratio and increase the frequency of Treg cells. 28 , 29 Treg cells in the breast cancer were positively associated with disease progression, and the CD8+/Treg ratio was associated with lymph node metastasis and tumor staging. 31 Treg cells are considered immuno-suppressive cells, similar to Th2 cells.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Moreover, sufentanil may decrease the CD4 + /CD8 + ratio and increase the frequency of Treg cells. 28 , 29 Treg cells in the breast cancer were positively associated with disease progression, and the CD8+/Treg ratio was associated with lymph node metastasis and tumor staging. 31 Treg cells are considered immuno-suppressive cells, similar to Th2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, heroin users show reduced CD4 + T cell proliferative activity upon stimulation in vitro and an altered Th1/Th2 balance when compared with healthy controls and individuals on opioid maintenance therapy (Sacerdote et al, 2008;Riß et al, 2012). In rats, acute morphine exposure (Peng et al, 2020) and moderate doses of naltrexone (Xu et al, 2020) have been shown to suppress Th17 cell expression and function, as well as disrupt the balance between Th1 and Th2 cells (Xu et al, 2020). Moreover, treatment with chronic morphine enhances Th17 cell functional activity in peripheral blood mononuclear cells isolated from non-human primates (Cornwell et al, 2013).…”
Section: Clinical Use Of Opioids and Immunomodulationmentioning
confidence: 87%
“…Altered Treg cell numbers have been reported in tobacco use related diseases including increased Treg cell numbers in pulmonary lymphocyte follicles of moderate COPD patients ( 8 ), increased Foxp3 + Treg cells in large airways but decreased in small airways (main pathological sites in COPD) ( 9 , 10 ), and decreased Treg cell numbers in the blood of patients with severe COPD ( 13 ), suggesting that the chronic inflammation in these patients may be promoted by lack of this regulatory cell population. In addition, studies revealed that M use alters T cell compartmentation and function, including the Treg cell component ( 20 , 42 ). Our study observed that both SM and M alone increased the proportion of Treg cells in spleen, and SM increased the percentage of Treg cells in LN.…”
Section: Discussionmentioning
confidence: 99%